Efficient utilization of coal slime using anaerobic fermentation technology. (July 2021) - Guo, Hongyu; Zhao, Shufeng; Xia, Daping; Wang, Lei; Lv, Jinghui; Yu, Hongfei; Jiao, Xiaojian
Highlights: New idea for the efficient utilization of coal slime is proposed. Anaerobic fermentation converted the organic matter in coal slime to biogas. Dehydration characteristics improved after biodegradation. Combustion performance improved after biodegradation. Abstract: In order to increase the utilization of coal slime, realize efficient utilization of resources and protect the environment, the feasibility of anaerobic fermentation technology employing coal slime was explored. The biodegradation of coal slimes and its influence on the utilization characteristics were analyzed using biogas production simulations, drying dehydration and thermogravimetric (TG) analysis. The results showed that the organic matter in various coal slimes could be converted to biomethane. In addition, the main methanogenic pathway was the reduction of CO2 . Moreover, lower the metamorphic degree of coal slimes and higher the ash content, more conducive were they to the dehydration of coal slimes. After biodegradation, the temperatures of four coal slimes during the stages of release of moisture, volatile combustion, residual coke combustion and burnout advanced to varying degrees. Moreover, the combustion performance improved. The research results provided a novel idea for the efficient utilization of coal slime.